The Role of Political Leadership in Crisis Management: Lessons From Global Pandemics - Daniel Pasaribu (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Political leadership plays a pivotal role in determining the effectiveness of crisis management, particularly during global pandemics that require swift, coordinated, and evidence-based responses. This study investigates the influence of political leadership styles, decision-making approaches, and governance structures on the management of pandemics such as COVID-19, H1N1, and Ebola. Using a comparative qualitative approach, data were collected from official policy documents, public speeches, and international health reports to identify patterns of leadership behavior and their impact on public health outcomes. The findings reveal that leaders who demonstrated transparent communication, strong intergovernmental collaboration, and adaptive policy-making achieved more effective containment and recovery results. Conversely, leadership characterized by delayed responses, politicization of health measures, and lack of trust-building often exacerbated the crisis. This research contributes to the understanding of how political leadership can shape crisis trajectories, offering lessons for future global health emergencies. The implications suggest that leadership training, evidence-based decision-making, and institutional resilience are critical for mitigating the socio-economic and health impacts of pandemics.